Delokalizacja przedsiębiorstw - efekt globalizacji - Małuszyńska, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
At session of 14.07.2005 the EESC adopted the own-initiative opinion "The scope and effects of company relocation". A firm relocation, a stage of a firm life cycle, is a direct cause of job losses and brings such problems as an increase in social security costs for governments and increase of social exclusion and less economic growth of countries and regions. On the other hand a business relocation can help to promote social rights in countries receiving investments, involves the regular transfer of know-how and increases the competitiveness of the relocated businesses. The main directions of business relocations are: Southeast Asian countries, countries with emerging economies - particularly China and new member states of the European Union. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 204-213